A taxonomic revision of the genus Hexarhopalus (Coleoptera, Tenebrionidae: Cnodalonini) from China - Jiang, Ri-Xin; Bai, Xing-Long; Ren, Guo-Dong; Yang, Hui-Yu; Wang, Shuo (Zootaxa, 2020)
Chinese components of the genus Hexarhopalus Fairmaire, 1891 are revised. Four new species, Hexarhopalus (Hexarhopalus) liuyixiaoi Jiang, Bai, Ren & Wang sp. nov. from Hunan and Hubei, Hexarhopalus (Leprocaulus) qiujianyueae Jiang, Bai, Ren & Wang sp. nov. and Hexarhopalus (Leprocaulus) qiului Jiang, Bai, Ren & Wang sp. nov. from Yunnan and Hexarhopalus (Leprocaulus) xuhaoi Jiang, Bai, Ren & Wang sp. nov. from Xizang are described, figured and compared with their congeners. Hexarhopalus (Leprocaulus) difformis (Pic, 1922) is recorded from Yunnan, China for the first time. New distributional records are provided for Hexarhopalus (Leprocaulus) bisinuatus Ren & Xu, 2011 from Hunan, Sichuan and Fujian, China. Supplementary description is presented for Hexarhopalus (Hexarhopalus) sculpticollis Fairmaire, 1891, Hexarhopalus (Hexarhopalus) sculptilis Kaszab 1960 and Hexarhopalus (Leprocaulus) difformis (Pic, 1922) to include the genital characters. A checklist, key and the distribution map of all known Chinese Hexarhopalus species are also provided.